PENDEKATAN KONSTRUKTIVIS DALAM LINGKUP PEMBELAJARAN PENDIDIKAN SENI BUDAYA (SENI RUPA) - Yusri, Muhammad (Kreatif, 2014)
Abstract: The role of teachers is symbolically in line with the procewss of climbing a ladder it is the teachers who prepare the ladder, train the children to climb the whole levels of the ladderm to keep in balance, to be safe in going to the top. The teachers are demanded to do it himself / herself first, and become a model or a volunteer in order to show the students how to become a ladders master. On the other hand, the students as the subjects of the training will use their knowledge, skill, experience to go up the ladders. And this way of  ‘ladders-construction, ladder-going up’ is the basic principle of Constructivism is a school of learning which explains how the students learen. In the view of constructivism, the students or learners understand arts thorugh real or direct activities in arranging experiences in forms of hands-on and minds-on as well. The activities of arts involvement ( for the students ) is relatid to or attached on their sociocultural context within live which the students live since the arts experiences they have got will become a capital in order to constructthe conceptual understanding. Constructivism approaachin the learning of visual art / culture seemed  to be impossible whithout any realation on the context of local arts, considering that arts is one of the so manycultural products. On the other hand, arts/cultural learning which is based on local culture will create a more meaningful learning, and on the peak of that ; students will not alienated from their own cultural roots.   Keywords : constructivism, learning of arts.